1997
DOI: 10.1002/(sici)1097-4628(19970509)64:6<1161::aid-app16>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and thermal stability of novel anion exchange resins with spacer chains

Abstract: Spacer-modified anion exchange resins were prepared by suspension copolymerization of v-bromoalkylstyrenes or v-bromoalkyloxymethylstyrenes with 2-8 mol % of divinylbenzene, followed by quaternization with trimethylamine. The thermal stability of the spacer-modified anion exchangers of the OH form was examined by standing the resins in deionized water at 100-140ЊC for 30-90 days. The anion exchangers with alkylene chains such as butylene or heptylene groups between the benzene ring and the quaternary nitrogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 4 publications
0
47
0
Order By: Relevance
“…The improved stability of these types of cations has been supported by computational calculations using model compounds which revealed that attachment of quaternary ammonium groups to the polymer backbone having an alkyl spacer of >3 carbon atoms can lead to improved alkaline stability of the cation. 39,40 Recently, Hibbs and co-workers reported a similar stability result for a poly(phenylene) backbone with trimetylalkylammonium cations attached by a hexamethylene spacer. 41 Although the comb-shaped PPO membranes showed promising properties as AEMs, poor mechanical properties were observed for high IEC (>2.0 meq/g) membranes probably due to the poor compatibility between long alkyl side chain and PPO backbone.…”
Section: ■ Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…The improved stability of these types of cations has been supported by computational calculations using model compounds which revealed that attachment of quaternary ammonium groups to the polymer backbone having an alkyl spacer of >3 carbon atoms can lead to improved alkaline stability of the cation. 39,40 Recently, Hibbs and co-workers reported a similar stability result for a poly(phenylene) backbone with trimetylalkylammonium cations attached by a hexamethylene spacer. 41 Although the comb-shaped PPO membranes showed promising properties as AEMs, poor mechanical properties were observed for high IEC (>2.0 meq/g) membranes probably due to the poor compatibility between long alkyl side chain and PPO backbone.…”
Section: ■ Introductionmentioning
confidence: 75%
“…It is assumed that the degradation of these materials was a result of typical direct nucleophilic substitution and/or β-hydrogen Hofmann elimination that occurs for quaternary ammonium moieties where the Hofmann elimination might also provide a pathway for the observed cross-linking and insolubility of the CyDx samples. 39,40 The bicarbonate conductivities of comb-shaped CyDx membranes remainted at ∼80% of their initial values after the test of 2000 h while the conductivity of the BTMA20 membane decreased rapidly to ∼40% of the initial value after only 80 h (Figure 9a). This degradation behavior suggested that the comb-shaped membranes with one long alkyl side chain have much better alkaline stability than the BTMA membranes, and have sufficient long-term stability for AEM fuel cell applications.…”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
See 1 more Smart Citation
“…This poor stability in alkaline conditions derives from the strong nucleophilicity of the OHanions, which induces displacement (S N2 , or via ylide intermediates) and Hofmann elimination reactions (predominantly the latter when ß-hydrogens present). [18][19][20][21] With the aim of obtaining AAEMs with enhanced stability, alternative cationic head-groups including guanidinium, 22,23 stabilized phosphonium, 24,25 and imidazolium, [26][27][28][29][30] have been recently investigated. Zhang and co-workers reported a new class of AAEMs containing guanidinium head-groups, which maintained ionic conductivity even after immersion in aqueous NaOH (1 mol dm -3 ) for a week at room temperature; this suggested good alkaline stability.…”
Section: Introductionmentioning
confidence: 99%
“…As a result organic ion exchange resins are developed extensively [8][9][10][11] and various aspects of ion exchange technologies have been continuously studied to improve the efficiency and economy in various technological applications [5,6,12,13]. Development and synthesis of new organic ion exchange resins is usually followed by their characterization .…”
Section: Introductionmentioning
confidence: 99%